Egocentric bias across mental and non-mental representations in the Sandbox Task. Issue 11 (November 2018) - Samuel, Steven; Legg, Edward W; Lurz, Robert; Clayton, Nicola S
In the Sandbox Task, participants indicate where a protagonist who has a false belief about the location of an object will look for that object in a trough filled with a substrate that conceals the hidden object's location. Previous findings that participants tend to indicate a location closer to where they themselves know the object to be located have been interpreted as evidence of egocentric bias when attributing mental states to others. We tested the assumption that such biases occur as a result of reasoning about mental states specifically. We found that participants showed more egocentric bias when reasoning from a protagonist's false belief than from their own memory, but found equivalent levels of bias when they were asked to indicate where a false film would depict the object as when they were asked about a protagonist's false belief. Our findings suggest that that egocentric biases found in adult false belief tasks are more likely due to a general difficulty with reasoning about false representations than a specialised difficulty with reasoning about false mental states.